Efficacy of Mechanical Vibration of Heel Stick Pain in Neonates - KARAKOÇ, AYŞE (AVES PRESS LTD, 2018)
Objective: One of the most frequently observed painful procedures during newborn hospitalization is the neonatal heel prick. The use of vibration therapy in newborn pain control can be a preferred method for its non-invasive, cheap, and easy applicability. This study aimed to evaluate effectiveness of mechanical vibration application to avoid pain sensation during heel puncture in newborns. Methods: This was a prospective single-center, placebo-controlled,, prospective randomized study. The study sample composed of healthy neonates born between 37 and 42 weeks of gestation in Medeniyet University Goztepe Training and Research Hospital. Sixty healthy neonates born in the study hospital between September 2012 and March 2013 and who matched the inclusion criteria after parental consent was obtained were included in the study. Heel puncture was applied to the infants during routine testing for phenylketonuria. It was recorded that all of the newborns demographic characteristics, heart rate, oxygen saturation and body tempature measurement at the process. All applications was saved to video camera, then displayed followed and the NIPS was scored by the investigator. The Cronbach's alpha coefficient for the NIPS scoring system was 0.85 during the procedure and 0.87 after the procedure in this study. Results: Before procedure and during procedure the NIPS point average of the experiment group is calculated by (0.967+/-1.771) and (1.733+/-2.050). For the control group, before and during application the NIPS point average is (3,567+/-1,775) and (4,533+/-1,907), respectively (p<0.05). In both groups Newborns post-procedure NIPS score results was higher than during procedure NIPS score and it was statistically significant (p<0.05). Conclusion: Mechanical vibration is found to be effective in decreasing pain sensation in neonates.
Keywords: Pain; pain scale; sucrose; mechanical vibration; newborn